Challenges Faced by Students and Teachers in Utilizing Digital Technologies For Enhancing Map Reading and Interpretation Skills: (A Case of Kisarawe District, Tanzania) - Clement Maganga; Ashwarya Srivastava (Journal of Education and Teacher Training Innovation, 2025)
Background: The integration of digital technologies in geography education has shown promise, with tools such as Google Maps, and Google Earth enhancing map reading abilities. However, secondary schools in Tanzania encounter obstacles including limited digital resources, inadequate internet connectivity, and insufficient teacher training, which impede effective implementation. The study aimed to explore those challenges in secondary schools of Tanzania. Methods: This research employed a mixed-methods approach, integrating quantitative and qualitative techniques. Statistical analyses, including Chi-Square and Wilcoxon Signed-Rank tests, were used to examine relationships between variables, while surveys, interviews, and observations provided more comprehensive insights. Thematic analysis identified key challenges, such as training inadequacies, financial limitations, and policy shortcomings. Results: Indicated that the digital divide and poor infrastructure were the most significant hurdles, followed by insufficient teacher training and financial constraints that limited access to digital tools. Responses regarding policy alignment were mixed, while resistance to change was a minor issue. Language barriers and motivation also played a role in digital adoption. Conclusion: Despite these obstacles, educators recognize the potential of digital tools to enhance geography education. Statistical analysis revealed no significant correlation between specific challenges and teachers' attitudes, suggesting a willingness to embrace technology given adequate support. Overcoming these barriers is essential for successfully incorporating digital technologies into geography education in Tanzania's secondary schools.